Pengaruh Pemberian Tepung Daun Indigofera Sebagai Pengganti Bungkil Kedelai Dan Dedak Dalam Ransum Terhadap Sifat Kualitatif Dan Kuantitatif Entog (Cairina moschata) - Ujang Karna Wijaya; Dini Widianingrum; Oki Imanudin (Tropical Livestock Science Journal, 2023)
This study was conducted to analyze the effect and level of indigofera leaf flour as a substitute for soybean meal and rice bran in the ration on qualitative and quantitative properties. This research was conducted on March 30, 2021 to April 27, 2021. The study was conducted experimentally using a Completely Randomized Design (CRD). This study consisted of five types of treatment in the form of ration formulations, namely P0 = without the addition of indigofera leaf meal (TDI) as control feed, P1 = 25% addition of TDI, P2 = 50% addition of TDI, P3 = 75% addition of TDI and P4 = 100% the addition of TDI was given to 80 muscovy duck placed in cages that had been divided into 20 parts, each part was filled with 4 muscovy ducks. The variables observed in this study were qualitative traits including coat color, beak color, shank color, caruncle color and skin color and quantitative traits included body weight, body circumference, beak length, chest length, femur length, tibia length, tibia circumference, length shank and wing length. The data from the qualitative research were analyzed descriptively, while the quantitative traits were analyzed using the Analysis of Variance or Anova (Analysis of Variane) and further tested using the Duncan Multiple Range Test. The results showed that the provision of indigofera leaf flour in the ration at P4 showed a shiny and thicker coat color and had a significant effect on tibia circumference (P<0.05)